2002
DOI: 10.5326/0380321
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Injury Following a Horse Kick to the Head in Two Dogs

Abstract: Two dogs were presented to North Carolina State University Veterinary Teaching Hospital following blunt trauma to the head delivered by a horse kick. On presentation, both dogs had resolving clinical signs directly related to the head trauma, but both also had compromise to their upper airway as a result of indirect injury to the soft tissues of the neck, visible on plain radiographs. One dog made a full recovery following a period of assisted ventilation. The other dog was euthanized at the request of the own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It has been reported that approximately 1 to 2 per cent of all the dogs admitted to veterinary hospitals have injuries to the spinal cord resulting from intervertebral disc disease (Hoerlein 1953, Priester 1976) and there are many other conditions which can result in injuries to the spinal cord. They involve conditions that cause compression, concussion or laceration of the spinal cord, and include congenital vertebral instabilities (Jeffery and McKee 2001, De Risio and others 2002), penetrating or non‐penetrating traumatic injuries (McKee 1990, Shores 1992, Bagley and others 1999, Olby and others 2002), acquired conditions causing stenosis of the vertebral canal (De Risio and Olby 2000), neoplasia (Lane and others 1994, Jeffery and Phillips 1995), intraspinal synovial and ganglion cysts (Levitski and others 1999a, b, Webb and others 2001), and arachnoid cysts (Webb 1999, Rylander and others 2002). Although they have not been reported in dogs and cats, potentially life‐threatening conditions, for example, autonomic dysreflexia (Weaver and others 2002), or painful conditions can develop as a result of spinal cord injury in animals (Christensen and Hulsebosch 1997, Hulsebosch and others 2000).…”
mentioning
confidence: 99%
“…It has been reported that approximately 1 to 2 per cent of all the dogs admitted to veterinary hospitals have injuries to the spinal cord resulting from intervertebral disc disease (Hoerlein 1953, Priester 1976) and there are many other conditions which can result in injuries to the spinal cord. They involve conditions that cause compression, concussion or laceration of the spinal cord, and include congenital vertebral instabilities (Jeffery and McKee 2001, De Risio and others 2002), penetrating or non‐penetrating traumatic injuries (McKee 1990, Shores 1992, Bagley and others 1999, Olby and others 2002), acquired conditions causing stenosis of the vertebral canal (De Risio and Olby 2000), neoplasia (Lane and others 1994, Jeffery and Phillips 1995), intraspinal synovial and ganglion cysts (Levitski and others 1999a, b, Webb and others 2001), and arachnoid cysts (Webb 1999, Rylander and others 2002). Although they have not been reported in dogs and cats, potentially life‐threatening conditions, for example, autonomic dysreflexia (Weaver and others 2002), or painful conditions can develop as a result of spinal cord injury in animals (Christensen and Hulsebosch 1997, Hulsebosch and others 2000).…”
mentioning
confidence: 99%
“…6 Hypoventilation with cervical spinal cord injury has been reported in dogs. [1][2][3]7 The dog described in the present report received early clinical recognition and intervention after the traumatic episode, support during transport, appropriate referral to specialty centers, and rehabilitation; these factors are described in emergency medical systems as the chain of survival. 8 Ventilatory support has been described in dogs with cervical spinal cord disease and hypoventilation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Ventilatory support has been described in dogs with cervical spinal cord disease and hypoventilation. [1][2][3]7 In those studies and others [9][10][11][12][13][14][15] regarding PPV in dogs, no dogs were ventilated for > 14 days. However, similar to previous reports 2,13-14 of dogs with hypoventilation, the dog reported here was mostly ventilated in a synchronized intermittent mandatory ventilation mode and had similar PIP and V T .…”
Section: Discussionmentioning
confidence: 99%